Empowering Education in India: : Rethinking Access to Equity and Inclusivity through the Samagra Shiksha Abhiyan - Hoque, Md Asraul; Chalil, Krishnan (Voices of Teachers and Teacher Educators, 2024)
The Samagra Shiksha Abhiyan (SSA), evolving into the Samagra Shiksha scheme, marks a significant government initiative to enhance inclusive, quality education across India. This study critically examines its impact on promoting equitable learning opportunities, analyzing literature and government reports to evaluate key areas: infrastructure development, teacher training, and curriculum improvement. These elements are essential for fostering inclusive environments that address diverse learner needs, and supporting India’s sustainable development goals by reducing gender, socio-economic, and geographic disparities. Data is primarily drawn from secondary sources, i.e. empirical data as reported in the Lok Sabha sessions. The research identifies both successes and challenges in Samagra Shiksha’s inclusive practices. While the scheme has expanded access, persistent gaps in quality and inclusivity remain, largely due to resource allocation, teacher readiness, and community engagement. Overall, Samagra Shiksha is transforming education access nationwide, yet sustained efforts are essential for achieving true educational equity. This study contributes by highlighting achievements, limitations, and pathways for advancing inclusive quality education in India...